Positively and Negatively Charged Collagen Nanohydrogels: pH‐responsive Drug‐releasing Characteristics - Kim, Han‐Sem; Kim, Sung‐Jin; Kang, Ji‐Hye; Shin, Ueon Sang (Bulletin of the Korean Chemical Society, 2018)
Researchers are facing many challenges in developing a strategy for site‐specific delivery in the gastrointestinal tract that can maximize therapeutic response and reduce side effects. The objective of this article was to develop a site‐specific drug delivery system for the gastrointestinal tract using natural polymer collagen (CG). For this, two types of pH‐responsive CG nanohydrogels (negatively charged pH‐CGNH‐COOH and positively charged pH‐CGNH‐NH2) were prepared using negatively and positively functionalized carbon nanotubes, CNT‐COOH and CNT‐NH2, respectively. The pH‐CGNH‐COOH and pH‐CGNH‐NH2 nanohydrogel samples comprising negatively and positively charged fibrils (CG/CNT‐COOH and CG/CNT‐NH2) were physicochemically characterized by Fourier‐transform infrared spectrometry, Zeta sizer, thermogravimetric analysis, and field emission scanning electron microscopy. They also revealed the pH‐responsive release of bovine serum albumin at pH 9 and cytochrome C at pH 2. These results strongly indicate that these drug carriers can be useful for site‐specific delivery in the gastrointestinal tract.